Creating mobile apps with jquery mobile : create fully responsive and versatile real-world apps for smartphones with jquery mobile 1.4.5 /: create fully responsive and versatile real-world apps for smartphones with jquery mobile 1.4.5. (2015) - Matthews, Andy; Shane Glise
No abstract available